Polish Help to Jews in the Countryside during the German Occupation. A Sketch Using the Example of the Righteous among the Nations - Zuzanna Schnepf-Kołacz (Zagłada Żydów)
The author analyzes help by Poles decorated with the Righteous among the Nations medal to Jews hiding in the countryside during the Nazi occupation. The author demonstrates that stories told many years later differ from immediate post-war recollections. A statistical analysis of the extensive material yields information on the various regularities related to help in rural areas: that the scale of help depends on the integration of the Jews with the Polish society, that they most often sought help close to their places of residence, that help came more frequently form the peasants than from the educated village dwellers, and that the greatest threat to the helpers were their own neighbors.